Accuracy and safety of CT guided transthoracic needle biopsy - Nema, Mustafa; Fadhil, Atheer A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background:Image guided transthoracic needle biopsy (TTNB) has great diagnostic value for the definitive characterization of lung lesions and is an established primary procedure to diagnose pulmonary nodules. It is traditionally performed as an outpatient procedure. It is safe, accurate, sensitive, and can obviate surgical procedure. Objective: to assess the accuracy and safety of CT-guided TTNB in Baghdad Teaching Hospital Patients & Methods: From December 2009 to September 2011, we conducted a prospective study of 43 consecutive outpatient and inpatient lung biopsies. An informed consent was obtained from the patients. No sedation is required. All biopsies were performed using CT guidance without CT fluoroscopy and were performed under local anesthesia using a 16 gauge core biopsy needle with internal automated gun. A posteroanterior inspiratory CXR was obtained 30 minutes after biopsy. All complications were recorded. If there was no pneumothorax, the patient was discharged. If there was a small asymptomatic pneumothorax, serial radiographs has been performed, patients also were discharged if no change in size was noted. Results: A total of 43 patients underwent CT guided TTNB of peripheral lung lesions (mean age 60 years) and a male to female ratio of 28:15. The operation was successful in 40 out of 43 patients. The sample was adequate in 39 out of 43 patients. Complications were recorded in 4 patients (the most common complication was pneumothorax). No patient needed chest tube insertion. Conclusion: CT guided TTNB is safe and an accurate procedure and can be performed as an outpatient procedure under local anesthesia.